Beyond cancer genes: colorectal cancer as robust intrinsic states formed by molecular interactions. Issue 11 (8th November 2017) - Yuan, Ruoshi; Zhang, Suzhan; Yu, Jiekai; Huang, Yanqin; Lu, Demin; Cheng, Runtan; Huang, Sui; Ao, Ping; Zheng, Shu; Hood, Leroy; Zhu, Xiaomei
Abstract : Abstract : Colorectal cancer (CRC) has complex pathological features that defy the linear-additive reasoning prevailing in current biomedicine studies. In pursuing a mechanistic understanding behind such complexity, we constructed a core molecular–cellular interaction network underlying CRC and investigated its nonlinear dynamical properties. The hypothesis and modelling method has been developed previously and tested in various cancer studies. The network dynamics reveal a landscape of several attractive basins corresponding to both normal intestinal phenotype and robust tumour subtypes, identified by their different molecular signatures. Comparison between the modelling results and gene expression profiles from patients collected at the second affiliated hospital of Zhejiang University is presented as validation. The numerical 'driving' experiment suggests that CRC pathogenesis may depend on pathways involved in gastrointestinal track development and molecules associated with mesenchymal lineage differentiation, such as Stat5, BMP, retinoic acid signalling pathways, Runx and Hox transcription families. We show that the multi-faceted response to immune stimulation and therapies, as well as different carcinogenesis and metastasis routes, can be straightforwardly understood and analysed under such a framework.